How to improve the histopathological diagnosis of systemic vasculitides in daily practice? - Honsová, Eva (Ceskoslovenska patologie, 2020)
The most common group of systemic vasculitides in adulthood are anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV). AAV represent autoimmune systemic vasculitides and include 3 clinical phenotypes: Granulomatosis with polyangiitis (GPA, formerly Wegener granulomatosis), Microscopic polyangiitis (MPA) and Eosinophilic granulomatosis with polyangiitis (EGPA, formerly Churg-Strauss syndrome). Histological features are similar to each other in all affected locations, and there are represented by necrotizing vascular inflammation of small and medium calibers, often venules, capillaries or arteriols, typically with fibrinoid vessel wall necrosis. The consequences of this condition are bleeding, as well as compromise of the lumen which may result in downstream tissue ischemia and necrosis. Typically affected locations in biopsy practice are: ENT, lung, skin, GIT, and kidney. The aim of this review is to provide a comprehensive overview of the important histopathological findings. ANCA positive vasculitis is a serious life-threatening disease and therefore requires a rapid diagnosis and appropriate therapy.
Keywords: ANCA positive vasculitis; Adult; dospělí; GPA; Churgův-Straussové syndrom; protilátky proti cytoplazmě neutrofilů; granulomatóza s polyangiitidou; ANCA-asociované vaskulitidy; mikroskopická polyangiitida; Anti-Neutrophil Cytoplasmic Antibody-Associated Vasculitis; Granulomatosis with Polyangiitis; Humans; lidé; histopathology; Antibodies, Antineutrophil Cytoplasmic; Churg-Strauss Syndrome; MPA; Microscopic Polyangiitis